Preparation and Tribological Performance of the Ag/BN Nanocomposite as Additives for Lithium-Based Grease - Yijun Chen; Chuan Li; Xiaodong Wang; Li Zhang; Xu Tan; Yubin Peng; Xiaoyong Xu (Lubricants)
This study synthesized a nanocomposite composed of silver nanoparticles and boron nitride (Ag/BN nanocomposite) by depositing Ag nanoparticles on BN surfaces. The chemical composition, structure, micromorphology, and tribological properties of the Ag/BN nanocomposite were investigated using transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), Raman spectroscopy, and a high-speed reciprocating tribometer. Under a 10 N load, 30 min test duration, 50 mm/s sliding speed, and 2 wt% additive concentration, lithium-based grease (LBG) containing Ag/BN nanocomposite exhibited the lowest average friction coefficient of 0.33 and a wear rate of 1.08 × 10−14 m3/(N × m), representing reductions of 35.2% and 41.6%, respectively, compared to pure LBG. A further analysis of the friction mechanism was conducted using 3D laser scanning microscopy, scanning electron microscopy (SEM), and XPS. The results indicate that the Ag/BN nanocomposite effectively reduced friction and wear on the friction pair surfaces through repair mechanisms, the formation of lubricating films, and micro-bearing effects.